Brief Report: T-Cell Receptor α Repertoire Diversity at Birth After in utero Exposure to HIV Integrase Strand-Transfer Inhibitors. (1st March 2023) - de Villartay, Jean Pierre; Pannier, Emmanuelle; Sibiude, Jeanne; Frange, Pierre; Tubiana, Roland; Blanche, Stéphane
Abstract : Supplemental Digital Content is Available in the Text. Abstract: Effectiveness of anti-HIV in the prevention of perinatal transmission has been established. Assessing the tolerance of drug exposure during pregnancy is of the utmost importance given the number of children exposed. HIV integrase and the recombinase-activating gene enzyme involved in the establishment of the T-lymphocyte repertoire show structural similarity. The inhibition of recombinase-activating (RAG) gene by anti-integrases is observed in vitro, in a variable way according to the molecules. Here, we show that in utero exposure to raltegravir did not alter the T-lymphocyte repertoire of 12 newborns. These reassuring data merit verification for other anti-integrases. (ClinicalTrial.org NCT 04024150).